Analisis pertumbuhan benih ikan Jelawat (Leptobarbus hoevenii) dengan penambahan asam amino metionin dalam pakan - Pratama, Jatmiko; Nikhlani, Andi; Ma'ruf, Mohamad (e-Journal BUDIDAYA PERAIRAN, 2024)
This study aimed to determine the effect of the addition of methionine amino acids into feed with different doses on the growth rate of hoven’s carp (Leptobarbus hoevenii) and determine the best dose that improves the growth. The test fish was a hoven’s carp that was reared for 30 days. This study used a Completely Randomized Design (CRD) with 5 treatments. The treatments included: A (0.0%), B (0.1%), C (0.2%), D (0.3%), and E (0.4%).  The density of fish was 20 individuals per container by giving feed insatiation. The results of the study showed that the treatment of the addition of methionine amino acids in the feed had a significant effect on absolute weight growth, total length growth, specific growth rate, and feed conversion ratio (P< 0.05). Treatment E (0.4%) gave the best results of absolute weight growth (2.94 gr), total length growth, and (1.70 cm), specific growth rate (5.73%). Keywords: aquaculture, fish growth, methionine